Remarks on Receiving the 2003 AAPHD Distinguished Service Award - Louise M. E. Hogan (Blackwell Synergy, 2003)
How can I respond adequately to the kindness of your comments about my career in public health in service to the oral health of our national and international communities? It is I who need to thank all of you who accepted me as part of the team of players throughout these years